Activation of peroxisome proliferator‐activated receptor delta suppresses BACE1 expression by up‐regulating SOCS1 in a JAK2/STAT1‐dependent manner. Issue 3 (18th June 2019) - Lee, Won Jin; Ham, Sun Ah; Lee, Gyeong Hee; Choi, Mi‐Jung; Yoo, Hyunjin; Paek, Kyung Shin; Lim, Dae‐Seog; Hong, Kwonho; Hwang, Jung Seok; Seo, Han Geuk
Abstract: Neuronal expression of beta‐secretase 1 (BACE1) has been implicated in the progression of Alzheimer's disease. However, the mechanisms that regulate BACE1 expression are unclear. Here, we show that peroxisome proliferator‐activated receptor delta (PPARδ) decreases BACE1 expression by up‐regulating suppressor of cytokine signaling 1 (SOCS1) in SH‐SY5Y neuroblastoma cells. The activation of PPARδ by GW501516, a specific PPARδ agonist, inhibited expression of BACE1. This effect was abrogated by shRNA‐mediated knockdown of PPARδ and by treatment with the PPARδ antagonist GSK0660, indicating that PPARδ is involved in GW501516‐mediated suppression of BACE1 expression. On the other hand, GW501516‐activated PPARδ induced expression of SOCS1, which is a negative regulator of cytokine signal transduction, at the transcriptional level by binding to a PPAR response element in its promoter. This GW501516‐mediated induction of SOCS1 expression led to down‐regulation of BACE1 expression via inactivation of signal transducer and activator of transcription 1. GW501516‐activated PPARδ suppressed the generation of neurotoxic amyloid beta (Aβ) in accordance with the decrease in BACE1 expression. Taken together, these results indicate that PPARδ attenuates BACE1 expression via SOCS1‐mediated inhibition of signal transducer and activator of transcription 1 signaling, thereby suppressing BACE1‐associated generation of neurotoxic Aβ. Abstract : Neuronal expression of beta‐secretase 1 (BACE1) has been implicated in the progression of Alzheimer's disease. However, the mechanisms that regulate BACE1 expression are unclear. Here, we show that the activation of peroxisome proliferator‐activated receptor delta (PPARδ) up‐regulates suppressor of cytokine signaling 1 (SOCS1) expression via PPAR response elements, thereby suppresses janus kinase 2/signal transducer and activator of transcription 1 (JAK2/STAT1)‐mediated BACE1 expression leading to the reduction in amyloid‐beta (Aβ) generation. These findings support the hypothesis that PPARδ is a key therapeutic target in Aβ‐related neuronal disorders. Open Science: This manuscript was awarded with the Open Materials Badge For more information see: https://cos.io/our-services/open-science-badges/